Increasing the Discharge Rate Capability of Lithium-Ion Cells with Laser-Structured Graphite Anodes: Modeling and Simulation. Issue 7 (1st January 2018) - Habedank, Jan B.; Kraft, Ludwig; Rheinfeld, Alexander; Krezdorn, Christina; Jossen, Andreas; Zaeh, Michael F.
Abstract : A physical-chemical model is suggested, which is able to describe the enhanced discharge rate capability of lithium-ion cells by using laser-structured graphite anodes. Recently published test data of coin cells comprising unstructured and structured graphite anodes with LiNi1/3 Co1/3 Mn1/3 O2 cathodes is used for the presented purpose of modeling, simulation and validation. To minimize computational demand, a homogenized three-dimensional model of a representative hole structure is developed, accounting for charge and mass transport throughout the cell layers and one-dimensional diffusion within radial-symmetric particles. First, a standard pseudo-two-dimensional model is calibrated against rate capability test data of coin cells with unstructured anodes. The calibrated parameter set is transferred to the three-dimensional model in order to simulate the transient voltage response and the discharged capacity depending on the applied C-rate. The simulation data shows excellent agreement with experimental data for both cell types. Three stages of rate capability enhancement are identified showing an improved relative capacity retention of 11 − 24% at 3C. Experimental and simulation data reveal a restricted C-rate window, which can be positively affected by the structuring process, whereas both shape and pattern of the structuring process can be further optimized with the model.